Internationalization of training in International Relations in Brazil - André Luiz Coelho Farias de Souza; Vinicius Silva dos Santos; Alice Gravelle Vieira (Meridiano 47, 2017)
What are the characteristics of the concession policy for training abroad to the area of International Relations in Brazil between 1998 and 2013? In this direction, we resorted to the data obtained from the GeoCapes platform to observe the distribution of scholarship holders overseas in the areas of "Political Science and International Relations".